Phosphatidic acid, a versatile water-stress signal in roots - McLoughlin, Fionn; Testerink, Christa (Frontiers in Plant Science, 2013)
Adequate water supply is of utmost importance for growth and reproduction of plants. In order to cope with water deprivation, plants have to adapt their development and metabolism to ensure survival. To maximize water use efficiency, plants use a large array of signaling mediators such as hormones, protein kinases and phosphatases, Ca2+, reactive oxygen species and low abundant phospholipids that together form complex signaling cascades. Phosphatidic acid (PA) is a signaling lipid that rapidly accumulates in response to a wide array of abiotic stress stimuli. PA formation provides the cell with spatial and transient information about the external environment by acting as a protein-docking site in cellular membranes. PA reportedly binds to a number of proteins that play a role during water limiting conditions, such as drought and salinity and has been shown to play an important role in maintaining root system architecture. Members of two osmotic stress-activated protein kinase families, sucrose non-fermenting 1-related protein kinase 2 (SnRK2) and mitogen activated protein kinases (MAPKs) were recently shown bind PA and are also involved in the maintenance of root system architecture and salinity stress tolerance. In addition, PA regulates several proteins involved in abscisic acid (ABA)-signaling. PA-dependent recruitment of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) under water limiting conditions indicates a role in regulating metabolic processes. Finally, a recent study also shows the PA recruits the clathrin heavy chain and a potassium channel subunit, hinting towards additional roles in cellular trafficking and potassium homeostasis. Taken together, the rapidly increasing number of proteins reported to interact with PA implies a broad role for this versatile signaling phospholipid in mediating salt and water stress responses.